Natural and Synthetic Drugs Approached for the Treatment of Recurrent Aphthous Stomatitis Over the Last Decade - Vitamia C; Iftinan GN; Latarissa IR; Wilar G; Cahyanto A; Elamin KM; Wathoni N (Dove Medical Press, 2024)
Cszahreyloren Vitamia,1,2 Ghina Nadhifah Iftinan,3 Irma Rahayu Latarissa,4 Gofarana Wilar,4 Arief Cahyanto,5 Khaled M Elamin,6 Nasrul Wathoni1 1Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, Indonesia; 2Departement of Pharmacy, Akademi Farmasi Bumi Siliwangi, Bandung, Indonesia; 3Center of Excellence for Pharmaceutical Care Innovation, Universitas Padjadjaran, Sumedang, Indonesia; 4Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, Indonesia; 5Department of Restorative Dentistry, Faculty of Dentistry, Universiti Malaya, Kuala Lumpur, Malaysia; 6Graduate School of Pharmaceutical Sciences, Kumamoto University, Kumamoto, JapanCorrespondence: Nasrul Wathoni, Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Universitas Padjadjaran, Jl. Raya Bandung Sumedang KM 21, Jatinangor, 45363, Indonesia, Tel +622 842 888888 3510, Fax +622 842 888888, Email nasrul@unpad.ac.idAbstract: Recurrent aphthous stomatitis (RAS) refers to a sore and frequently recurring inflammation of the oral tissues, distinguished by the presence of small ulcers that cause significant discomfort and cannot be attributed to any underlying disease. Different treatments have been used for RAS. This review aims to provide a comprehensive overview of the treatment options over the past decade for recurrent aphthous stomatitis (RAS), encompassing both natural and synthetic treatments. It will utilize clinical efficacy studies conducted in vivo and in vitro, along with a focus on the pharmaceutical approach through advancements in drug delivery development. We conducted a thorough literature search from 2013 to 2023 in prominent databases such as PubMed, Scopus, and Cochrane, utilizing appropriate keywords of recurrent aphthous stomatitis, and treatment. A total of 53 clinical trials with 3022 patients were included, with 35 using natural materials in their research and a total of 16 articles discussing RAS treatment using synthetic materials. All the clinical trials showed that natural and synthetic medicines seemed to benefit RAS patients by reducing pain score, ulcer size, and number of ulcers and shortening the healing duration.Keywords: recurrent aphthous stomatitis, drug therapy, natural products, treatment outcome, clinical trial